Time-course morphological and functional disorders of the kidney induced by long-term high-fat diet intake in female rats - Pinhal, Carolina Staut; Lopes, Agnes; Torres, Daniele Bráz; Felisbino, Sergio Luis [UNESP]; Rocha Gontijo, José Antônio; Boer, Patrícia Aline [UNESP] (Oxford University Press (OUP), 2013)
BackgroundEvidence is emerging that highlights the far-reaching consequences of a high-fat diet (HFD) on kidney morphology and function disorders.MethodsThe present study was performed on 3-, 5-, 7- and 9-week-old HFD female rats compared with the appropriate gender and age-matched animals. We evaluated the kidney expression of angiotensin type II receptor and fibrotic and epithelial-to-mesenchymal transition (EMT) markers, by immunoblotting and immunohistochemical and histological techniques, in parallel with kidney function.ResultsIn the current study, the time-course HFD-treated group showed, by immunoblotting and immunohistochemical analysis, an early time-course increase in the expression of transforming growth factor β-1 (TGFβ-1) in the entire kidney of HFD-treated rats, compared with that observed in the control group. Simultaneously, the study shows a transient increase in the expression of ZEB2 in the HFD whole kidney accompanied by a fall in the E-cadherin expression and increased collagen and fibronectin deposition. A pronounced decrease in fractional urinary sodium excretion was also demonstrated in the long-term HFD-treated rats. The decreased FENa + was accompanied by a fall in FEPNa + and FEPP Na +, which occurred in association with significantly decreased CCr and, certainly on the sodium-filtered load. The reduction in the glomerular filtration rate (GFR) occurred in parallel to proteinuria and glomerular desmin overexpression.ConclusionsThe results of the current study suggest that podocyte injury in parallel with observed proteinuria and evidence of EMT transformation are associated with long-term loss of kidney function and renal sodium and water retention. © 2013 The Author. All rights reserved.
Keywords: epithelial-to-mesenchymal transition; high-fat diet; kidney fibrosis; renal function; TGFβ-1